The following questions came with only one instruction: simplify.
Question #2: (2x-5)(3x+2)
My answer: 5x-3
Question #3: (2x+5)(x^2-x-2)
Thanks in advance for your help!
Do #1 and #2 the same way as you started doing #3, but complete the job as Hallsofivy suggested. You need to complete the distribution and combine like terms.
Also, the site that Stroodle gave you is a good one. It appears that in #1 and #2 you are having a little trouble deciding if you should be multiplying or adding. Did you state them correctly? If you did, then you should be multiplying.
I believe your working should look something like this:
(x+2)(x+3)= x(x+3) + 2(x+3) = x^2 + 3x + 2x + 6 = x^2 + 5x + 6
(2x-5)(3x+2) = 2x(3x+2) -5(3x +2) = 6x^2 + 4x -15x -10 = 6x^2 -11x -10
(2x+5)(x^2-x-2) = 2x(x^2-x-2)+5(x^2-x-2)= 2x^3-2x^2-4x+5x^2-5x-10 = 2x^3+3x^2-9x-10